2019
DOI: 10.1101/599415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the protein dynamics and molecular determinants of iPSC-derived neurons

Abstract: Neuronal development is a multistep process with different regulatory programs that shapes neurons to form dendrites, axons and synapses. To date, knowledge on neuronal development is largely based on murine data and largely restricted to the genomic and transcriptomic level. Advances in stem cell differentiation now enable the study of human neuronal development, and here we provide a mass spectrometry-based quantitative proteomic signature, at high temporal resolution, of human stem cellderived neurons. To r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…The same methodology can be used to track the changes in the proteomic profile of other differentiation protocols. Varderidou et al used two iPSC to neuron differentiation protocols, expression of NGN2 to generate excitatory neurons and small molecules to generate motor neurons [135]. Interestingly, they compared both the proteome and transcriptome during neuronal differentiation and found that both methods have different signatures, highlighting significant differences between the RNA and protein levels within human engineered neurons.…”
Section: Proteomic Analysis Of 2d Human Ipsc-derived Neuron Culturesmentioning
confidence: 99%
“…The same methodology can be used to track the changes in the proteomic profile of other differentiation protocols. Varderidou et al used two iPSC to neuron differentiation protocols, expression of NGN2 to generate excitatory neurons and small molecules to generate motor neurons [135]. Interestingly, they compared both the proteome and transcriptome during neuronal differentiation and found that both methods have different signatures, highlighting significant differences between the RNA and protein levels within human engineered neurons.…”
Section: Proteomic Analysis Of 2d Human Ipsc-derived Neuron Culturesmentioning
confidence: 99%